Pengembangan Variasi Latihan Kekuatan pada Cabang Olahraga Panahan Kabupaten Kediri Usia 10-15 Tahun - Fenina Rahma Renata Islami; Imam Hariadi; Zumroh Hasanah (Pusat Riset dan Inovasi Nasional, 2024)
The aim of the research and development of this module is to develop physical training for archery sports referring to basic archery techniques. Researchers use the research and development model method in qualitative analysis and quantitative descriptive presentations that apply a Research and Development (R&D) design that refers to Borg and Gall. In this research, there are 7 research designs that are adapted to the characteristics studied, namely: 1) research and data collection, 2) planning, 3) product draft development, 4) small group trials, 5) initial product refinement, 6) large group trials , and 7) improvement of the final product. The product trial stages of this development module use 5 stages, namely: a) product refinement with evaluation results from 4 archery experts, b) small group research trial subjects using 4 athletes and 8 athletes for large group trials, c) types of research data using questionnaires, observation and documentation, d) Likert scale measurement techniques are data type instruments used in research, e) research data analysis techniques in the form of percentages. The validity results for archery experts show an average of 77.10%, which means this product is very valid. The module for developing variations in strength training for the archery sport in Kediri Regency aged 10-15 years was also tested in small groups with results of 79.85%, and large group trials showed a figure of 87.71%. The results of the large group trials and small group trials were categorized as valid, so the conclusion of the research on the development of strength training development modules for archery sports in Kediri Regency aged 10-15 years can be declared suitable for use in helping facilitate strength training in archery sports.